Strategi Promosi Usaha melalui Media Sosial Berbasis Desain Komunikasi Visual di Alfa Print - Zidan Alfaris; Sulartopo Sulartopo; Irdha Yunianto (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Social media has become a key channel for businesses to convey information about products and services to consumers. In this context, visual communication design plays a crucial role in message delivery through the various visual elements found in promotional content. This study aims to analyze the application of visual communication design in Alfa Print’s promotional content published on Instagram. A qualitative method with a descriptive approach was employed. Data were gathered through observation and documentation of the promotional content serving as the study's subject. The analysis examined visual communication design elements, including color, typography, layout, illustration, and visual messaging. The results indicate that Alfa Print’s promotional content effectively incorporates visual communication design elements when presenting information to the audience. Regarding color, the designs are dominated by blue—serving as the primary visual identity—complemented by yellow, red, and white to highlight key information. In terms of typography, the use of sans-serif typefaces and varying font sizes establishes a visual hierarchy that enhances readability. Regarding layout, the arrangement of visual elements creates a structured reading flow, although some content suffers from information overcrowding and suboptimal use of white space. As for illustrations, the use of visuals depicting products and printing services clarifies the information conveyed, though visual quality consistency requires improvement. Finally, the visual messaging successfully supports the communication of product and service information, although the strengthening of brand identity warrants further attention.